Randomized web‐based physical activity intervention in adolescent survivors of childhood cancer. Issue 8 (3rd May 2018) - Howell, Carrie R.; Krull, Kevin R.; Partin, Robyn E.; Kadan‐Lottick, Nina S.; Robison, Leslie L.; Hudson, Melissa M.; Ness, Kirsten K.
Abstract: Background: Healthy lifestyle choices, including participation in regular physical activity, may improve health outcomes in survivors of childhood cancer. We aimed to evaluate the efficacy of a web‐delivered physical activity intervention among adolescent survivors to increase moderate to vigorous physical activity (MVPA) and improve fitness and neurocognitive and health‐related quality of life (HRQoL) over 24 weeks. Procedure: This randomized controlled trial was conducted among survivors (aged ≥11 to <15 years) treated at a single institution. Participants were randomized to either a physical activity intervention delivered over the internet or a control group. The intervention group received educational materials, an activity monitor, and access to an interactive website designed to motivate increased physical activity via rewards; the control group received an activity monitor and educational materials. Physical activity, fitness, and neurocognitive and HRQoL outcomes were assessed at baseline and at 24 weeks. Mean changes were compared between groups using paired t ‐tests. Results: Of the 97 survivors enrolled, 78 completed the study; the mean age was 12.7 (standard deviation 1.1), 80% were White, and 55.1% were female. Fifty‐three survivors were assigned to the intervention and 25 to the control group. While survivors in the intervention group increased, and those in the control group decreased (4.7 ± 119.9 vs. –24.3 ± 89.7 min) weekly MVPA, this difference was not significant ( P = 0.30). However, hand grip strength, number of sit‐ups and pushups, neurocognitive function, and HRQoL outcomes improved in the intervention, but not in the control group. Conclusions: An interactive, rewards‐based intervention designed to increase MVPA is feasible in adolescent survivors of childhood cancer.